A novel methodology to characterize the constitutive behaviour of polyethylene terephthalate for the stretch blow moulding process. (January 2017) - Yan, Shiyong; Menary, Gary; Nixon, James
Highlights: A new characterization method for materials under blowing conditions is developed. The method relies on specialist instrumentation and digital image correlation. Constitutive behaviour of materials obtained solely by a preform during blowing. Abstract: The stretch blow moulding (SBM) process is the main method for the mass production of PET containers. And understanding the constitutive behaviour of PET during this process is critical for designing the optimum product and process. However due to its nonlinear viscoelastic behaviour, the behaviour of PET is highly sensitive to its thermomechanical history making the task of modelling its constitutive behaviour complex. This means that the constitutive model will be useful only if it is known to be valid under the actual conditions of interest to the SBM process. The aim of this work was to develop a new material characterization method providing new data for the deformation behaviour of PET relevant to the SBM process. In order to achieve this goal, a reliable and robust characterization method was developed based on an instrumented stretch rod and a digital image correlation system to determine the stress-strain relationship of material in deforming preforms during free stretch-blow tests. The effect of preform temperature and air mass flow rate on the deformation behaviour of PET was also investigated.